8x-2-x-4x=-3x+14

Simple and best practice solution for 8x-2-x-4x=-3x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-2-x-4x=-3x+14 equation:


Simplifying
8x + -2 + -1x + -4x = -3x + 14

Reorder the terms:
-2 + 8x + -1x + -4x = -3x + 14

Combine like terms: 8x + -1x = 7x
-2 + 7x + -4x = -3x + 14

Combine like terms: 7x + -4x = 3x
-2 + 3x = -3x + 14

Reorder the terms:
-2 + 3x = 14 + -3x

Solving
-2 + 3x = 14 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-2 + 3x + 3x = 14 + -3x + 3x

Combine like terms: 3x + 3x = 6x
-2 + 6x = 14 + -3x + 3x

Combine like terms: -3x + 3x = 0
-2 + 6x = 14 + 0
-2 + 6x = 14

Add '2' to each side of the equation.
-2 + 2 + 6x = 14 + 2

Combine like terms: -2 + 2 = 0
0 + 6x = 14 + 2
6x = 14 + 2

Combine like terms: 14 + 2 = 16
6x = 16

Divide each side by '6'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| x^3-3x^2+4x+y^3+6y^2+13y+8=0 | | 6p+18p=192 | | (8+3i)(8-3i)=0 | | 4x^2+20x+551=0 | | 2k-8=5-6k | | Log(x)=10 | | -6(2b+4)+(13b-9)=0 | | C(7)=300+7x | | 35x+2=25x-7+15x-8 | | 3.6q-3.1-4.1q=-1.5-3.8 | | v^2+6=-5v | | z^2-bz-az+ab=0 | | =10-4(4+a) | | 4n=-28n-3 | | 3-q+q=4q+27 | | 8a-5=11 | | 53-2d=2+d | | 4a^2-19+10=0 | | 3x^4-9x^3+15x^2=0 | | 3-2h=-7 | | 2m+107=6m+m+71 | | c=300+2x | | 10q-3q-4q=93-27+51 | | 9a+45=13a+a | | x+(x*.0229)=380.25 | | c(x)=300+7x | | 8(-4)-3=11(-4)+9 | | 24-7x=x+48-80 | | 12x^2-2x+15=0 | | v-2=15 | | 12=m+7 | | 10(0)+25y=1000 |

Equations solver categories